Exploration and Development of Unconventional Oil and Gas Resources: Latest Advances and Prospects (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This collection focuses on the latest advances and prospects in unconventional oil and gas (such as coalbed methane, shale gas, tight gas, heavy oil, hydrate, etc.) exploration and development, including favorable fracture evaluation, enhanced oil recovery, reservoir characterization, gas occurrence and extraction, hydrocarbon accumulation processes and modes, solvent exsolution and liberation, rare earth element distribution, sedimentary environment and organic matter enrichment model, diagenetic facies, and reservoir properties. Some new methods are proposed to improve deep coal seams’ gas extraction, characterize reservoir seepage ability, reveal organic rich shale’s formation mechanism, and cleverly identify the diagenetic facies of tight oil reservoirs, among others.